2000
DOI: 10.1002/1097-0215(20001120)89:6<488::aid-ijc4>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic significance in lung cancer of human tumor-associated antigen RCAS1

Abstract: A new monoclonal antibody (MAb), 22‐1‐1, acts against a novel tumor‐associated antigen (Ag) strongly expressed in human uterine cervical adenocarcinomas. A cDNA encoding the Ag recognized by the 22‐1‐1 MAb has been isolated and called RCAS1 (receptor‐binding cancer antigen expressed on SiSo cells). RCAS1 can induce growth arrest and apoptosis in RCAS1 receptor‐positive cells including T cells and natural killer cells in vitro. These results suggest that RCAS1 is involved in tumor escape from the immune system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
0
1

Year Published

2002
2002
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 16 publications
4
73
0
1
Order By: Relevance
“…The anti-RCAS1 monoclonal antibody strongly stained human uterine and ovarian carcinomas [3][4][5]. In nongynecological carcinomas, RCAS1 is also expressed in nonsmall-cell lung carcinomas, hepatocellular carcinomas, and squamous cell carcinomas of the skin [6][7][8]. In vitro studies of RCAS1 indicated that it might function as an apoptosisinducing factor, because binding between RCAS1 and its receptor induced apoptosis in receptor-expressing cells, including peripheral lymphocytes, such as T, B, and natural killer cells.…”
Section: Rcas1 (Receptor Binding Cancer Antigen Expressed Onmentioning
confidence: 99%
“…The anti-RCAS1 monoclonal antibody strongly stained human uterine and ovarian carcinomas [3][4][5]. In nongynecological carcinomas, RCAS1 is also expressed in nonsmall-cell lung carcinomas, hepatocellular carcinomas, and squamous cell carcinomas of the skin [6][7][8]. In vitro studies of RCAS1 indicated that it might function as an apoptosisinducing factor, because binding between RCAS1 and its receptor induced apoptosis in receptor-expressing cells, including peripheral lymphocytes, such as T, B, and natural killer cells.…”
Section: Rcas1 (Receptor Binding Cancer Antigen Expressed Onmentioning
confidence: 99%
“…RCAS1 induces apoptosis of lymphocytes by binding to a putative RCAS1 receptor . In addition, RCAS1 expression is associated with the number of apoptotic lymphocytes adjacent tumour cells in lung cancer and Hodgkin's disease (Iwasaki et al, 2000;Ohshima et al, 2001), and RCAS1 expression is inversely related with the degree of intratumoral infiltration of lymphocytes (Suzuki et al, 2001). In this study, TNF-a and Fas-L were little expressed in endometrial cancers.…”
Section: Discussionmentioning
confidence: 50%
“…Patients with RCAS1 overexpression had a poorer survival than those with normal RCAS1 expression and those with positive RCAS1 expression (Po0.0001). In previous studies, RCAS1 expression was associated with poorer clinical prognosis for uterine cervical adenocarcinoma and non-small-cell lung carcinoma (Kaku et al, 1999;Iwasaki et al, 2000;Izumi et al, 2001). RCAS1 expression has also been reported to correlate with tumour progression or the invasive tendency of uterine cervical, gastric, skin, and hepatocellular carcinomas (Sonoda et al, 1998;Kubokawa et al, 2001;Noguchi et al, 2001;Takahashi et al, 2001).…”
Section: Discussionmentioning
confidence: 91%
“…Recombinant and soluble RCAS1 inhibit cell proliferation and induce DNA fragmentation of PBLs. Moreover, fragmentation of the DNA in TILs has been observed in RCAS1-expressing human tumors (biliary adenocarcinoma, lung cancer, and gastric cancer) [5,6,13]. The majority of TILs in human tumors are T cells, suggesting an activation of the host defense mechanism [37].…”
Section: Discussionmentioning
confidence: 99%
“…RCAS1 has also been detected in nongynecological cancers such as human breast carcinomas [26,32,36], esophageal squamous cell carcinomas [19], gastric adenocarcinomas [6,16], hepatocellular carcinomas [2,21], lung cancers [13,14,22], and pancreatic adenocarcinomas [1,19]. Expression of RCAS1 is associated with a poor prognosis in these cancer patients.…”
mentioning
confidence: 99%